Wells–Dawson heteropolyacid supported on silica: isobutane alkylation with C4 olefins - Baronetti, Graciela Teresita (2001)
The alkylation of isobutane with C4 olefins is studied, using heteropolyacids (HPA) with Wells–Dawson (WD) structure supported on silica (WD/SiO2). The catalytic performance of these catalysts is compared with a lanthanum-exchanged Y-zeolite catalyst. The loading of the HPA on silica was varied between 9 and 28 wt.%. These catalysts have activity for trimethylpentanes (TMP) production. The selectivity towards these products is not as high as in the case of the lanthanum containing Y-zeolite. The acidity of WD/SiO2 catalysts increases as the loading increases, as seen by MAS-NMR. Correspondingly, a better TMP production is observed. The increase both in acidity and in the TMP production as a function of the WD content is more noticeable at low loading. The coke formed during the reaction requires high temperatures, 550°C approximately, in order to be fully removed with an oxygen containing carrier gas. The temperature-programmed oxidation (TPO) profile of this coke displays two peaks, the first one between 80 and 300°C associated with hydrocarbons that are released upon heating, and the second between 300 and 550°C, associated with coke that changed its structure during the heating. A regeneration at intermediate temperatures, e.g. 300°C, removes the coke that corresponds to the first peak, but does not restore the initial activity. If the regeneration is carried out at higher temperatures, e.g. 500°C, most of the coke is removed, but this treatment leads to changes in the structure of the HPA, as indicated by FTIR and MAS-NMR analysis. Regeneration with O3 at low temperature (125°C) is effective both for coke removal and to recover the catalytic activity.